ANALISIS FAKTOR INTERNAL DAN EKSTERNAL BANK YANG MEMPENGARUHI PROFITABILITAS BANK UMUM DI INDONESIA - Aris Fadjar; Hedwig Esti S; Tri Hartini EKP (Research Center and Case Clearing House PPM School of Management, 2013)
The purpose of this research is to analyze the influence of internal factors of banks consisting of Capital Adequacy Ratio (CAR), Non-Performing Loans (NPLs), Operating Expenses Operating Income (BOPO), Loan to Deposit Ratio (LDR), and external factors of banks consisting of the value exchange rate of rupiah against the U.S. dollar, interest rate (SBI 1 month), and the inflation rate to Return On Asset (ROA) of the general bank. It used the secondary data from Indonesia Economic and Financial Statistic (SEKI) which published by Bank Indonesia monthly. The samples took from ROA of general bank as series, CAR, NPLs, BOPO, LDR, inflation rate, exchange rate rupiah to US , and SBI rate with period 2007-2010. The result shows, external factors of banks and CAR do not significantly influence to the ROA of general Bank, while internal factors are significantly influence to ROA general bank. As the simultaneous, the seven variables have positive significant influence to the ROA general bank it can be proofed with F value > F table (7.574 > 2.589). And all of the independence variables have had influenced for 52.9 percent to the ROA general bank.